Islamic Civilization Park, Kuala Terengganu: attributes towards tourist satisfaction / Nabihah Juhari, Nur Effira Aida Azhari and Nik Nur Amirah Ibrahim - Juhari, Nabihah; Azhari, Nur Effira Aida; Ibrahim, Nik Nur Amirah (2015)
The concept of Islamic Tourism is deemed to be newly growth in the industry and the demand of Muslim tourists who travel and experience tourism related activities have brought forward a better understanding on their motivational factors. This is to provide better satisfaction for them when visiting Islamic tourist destination. Therefore, this research paper seeks to determine the motivational factor that influence visitor satisfaction with various products, and services of attractions offered in Islamic Civilization Park, Kuala Terengganu. The study used secondary data that was based on relevant literatures. Primary data was also being used based on quantitative. Data was collected through questionnaire and randomly given to the tourist in Kuala Terengganu to assess their satisfaction level. The findings of this study provide a better understanding on tourist satisfaction in Malaysian Islamic tourist destination by looking into three motivational factors include service quality, architectural design and monument of the place, and lastly destination attributes